The Role of Intramuscular Progesterone in the Prevention of Preterm Labor - صالح, حسن; أيوب, جهاد; عبد الله, علا (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: Premature birth before 37 weeks gestation is the leading cause of neonatal morbidity and mortality worldwide. Intramuscular progesterone administration has been considered effective in preventing preterm labor in high-risk women, especially with a previous PTB history and a short cervix in the middle trimester of pregnancy. Materials and Methods: The study included 50 pregnant patients between the week (20-24 W) divided into two groups: 23 patients given intramuscular progesterone at a dose of 250 mg weekly, 27 patients not taking intramuscular progesterone. Pregnant women were evaluated through an ultra sound to determine the number of fetuses, gestational age and fetal vitality and the amount of amniotic fluid and the length of the cervix were performed hemoglobin tests, liver enzymes, urine test and sediment analysis. Results: The percentage of the group exposed to intramuscular progesterone was 46% and for the control group 54%. The calculation of the relative risk of preterm birth was carried out in case of a previous preterm birth history and it was 0.76 and therefore lower in the exposure group compared to the control group. The effect of cervical length on the incidence of preterm labor in the exposure group was 100% if the cervical length was< 25 mm and 57.14% with cervical length 25-35 mm and 0% if it was >35mm. Conclusion: administration of intramuscular progesterone to prevent preterm labor in high-risk women a history of a previous spontaneous preterm birth with a cervical length >35 mm.